A Distributed Learning & Teaching Environment across Institutions based on Advanced Grid Portal Technology - Awang hj. Hamid , Dayang hjh. Tiawa; Islam, Md. Rajibul; Alias, Norma (2010)
This study presents web-based networked information and collaborative authoring architecture as Information and Knowledge Grids. This architecture is made possible by advanced open source grid portal software in conjunction with distributed parallel computing system. Using this advanced grid portal technology all the cluster servers of different institutions has been developed that configure themselves as a learning & teaching Grid environment. The distributed learning and teaching grid environment supports multiple independent course specific collaborative content, information and knowledge networks across distributed servers over the Internet and parallel computing system enhances the job performances. These are in the process of getting deployed in the inter-campus departments in University Technology Malaysia (UTM) for improving the quality of higher education as an initial stage. This Grid architecture provides reasonable and effective online assisted learning environment for the institutions in any subject. The paper describes in some details of the architecture of advanced grid portal based on parallel computing system, learning & teaching interactions and the processes of courses management over it.